Correction: Dehydrocoupling of phosphine-boranes using the [RhCp∗Me(PMe3)(CH2Cl2)][BArF 4] precatalyst: stoichiometric and catalytic studies (Chem. Sci. (2016) DOI: 10.1039/c5sc04150c) - Hooper, T; Weller, A; Beattie, N; Macgregor, S (Royal Society of Chemistry, 2016)
Correction for 'Dehydrocoupling of phosphine-boranes using the [RhCp∗Me(PMe3)(CH2Cl2)][BArF 4] precatalyst: stoichiometric and catalytic studies' by Thomas N. Hooper et al., Chem. Sci., 2016, DOI: 10.1039/c5sc04150c.